Pengaruh Motivasi Kerja, Budaya Organisasi Dan Kompetensi Kerja Terhadap Kinerja Pegawai Di Bagian Keuangan SKPD Pemerintahan Provinsi Riau - Prasetio, Bambang; Satriawan, Raja Adri; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the influence for work motivation , organizational culture and workplace competencies to employee performance with the object of research personnel at the Riau Provincial Government on education finance . The sampling method using purposive sampling techniques and sample penerikan using Slovin formula with 10% error level . The author conducted research based data retrieval techniques through questionnaires . Analysis of the data that I use is besifat Quantitative analyzes of data through multiple linear regression equation with t test and test persial R2dan collected data is processed with the help of the statistical program SPSS 17.0 . The results were obtained as a partial conclusion that three variables t ( 2.920 , 26.103 , and 2.901 ) to 3 variables showed t is greater than t table . It was concluded that all three variabel ( work motivation , organizational culture and workplace competencies ) in this study affect the performance of employees . Furthermore, seen from the determination of test where a R value of 0.937 and R2 of 0873 or 87.3 % . independent variables affect the dependent variable, was 12.7 % influenced by other variables .Keywords : Performance , work motivation , and Organizational Culture Competence